Erwinia carotovora Quorum Sensing System Regulates Host-Specific Virulence Factors and Development Delay in Drosophila melanogaster - Filipe J. D. Vieira (American Society for Microbiology, 2020)
ABSTRACT Multihost bacteria have to rapidly adapt to drastic environmental changes, relying on a fine integration of multiple stimuli for an optimal genetic response. Erwinia carotovora spp. are phytopathogens that cause soft-rot disease. Strain Ecc15 in particular is a model for bacterial oral-route infection in Drosophila melanogaster as it harbors a unique gene, evf, that encodes the Erwinia virulence factor (Evf), which is a major determinant for infection of the D. melanogaster gut. However, the factors involved in the regulation of evf expression are poorly understood. We investigated whether evf could be controlled by quorum sensing as, in the Erwinia genus, quorum sensing regulates pectolytic enzymes, the major virulence factors needed to infect plants. Here, we show that transcription of evf is positively regulated by quorum sensing in Ecc15 via acyl-homoserine lactone (AHL) signal synthase ExpI and AHL receptors ExpR1 and ExpR2. We also show that the load of Ecc15 in the gut depends upon the quorum sensing-mediated regulation of evf. Furthermore, we demonstrate that larvae infected with Ecc15 suffer a developmental delay as a direct consequence of the regulation of evf via quorum sensing. Finally, we demonstrate that evf is coexpressed with plant cell wall-degrading enzymes (PCWDE) during plant infection in a quorum sensing-dependent manner. Overall, our results show that Ecc15 relies on quorum sensing to control production of both pectolytic enzymes and Evf. This regulation influences the interaction of Ecc15 with its two known hosts, indicating that quorum sensing signaling may impact bacterial dissemination via insect vectors that feed on rotting plants. IMPORTANCE Integration of genetic networks allows bacteria to rapidly adapt to changing environments. This is particularly important in bacteria that interact with multiple hosts. Erwinia carotovora is a plant pathogen that uses Drosophila melanogaster as a vector. To interact with these two hosts, Ecc15 uses different sets of virulence factors: plant cell wall-degrading enzymes to infect plants and the Erwinia virulence factor (evf) to infect Drosophila. Our work shows that, despite the virulence factors being specific for each host, both sets are coactivated by homoserine lactone quorum sensing and by the two-component GacS/A system in infected plants. This regulation is essential for Ecc15 loads in the gut of Drosophila and minimizes the developmental delay caused by the bacteria with respect to the insect vector. Our findings provide evidence that coactivation of the host-specific factors in the plant may function as a predictive mechanism to maximize the probability of transit of the bacteria between hosts.